Aspectos relevantes da distrofia muscular do Golden Retriever para o estudo da distrofia muscular de Duchenne em humanos - De Moraes, Julieta Rodini Engrácia [UNESP]; Malvestio, Lygia Maria Mouri; Martins, Isabela Mancini [UNESP]; Mosko, Patrícia Regina Erdmann; Filho, Jair Rodini Engracia; De Moraes, Flávio Ruas [UNESP] (FapUNIFESP (SciELO), 2017)
Golden Retriever muscular dystrophy (GRMD) is the most representative model for studying Duchenne muscular dystrophy (DMD) in humans, owing its phenotypic expression. DMD is a recessive disorder linked to the X chromosome in which the loss of dystrophin induces progressive weakness and degeneration of the skeletal and cardiac muscles, which lead to replacement by connective and adipose tissues. Onset of clinical signs occurs between 2 and 5 years of age, and many patients die from heart or respiratory failure. The main studies concerning dystrophic Golden Retrievers (DGR) sought to elucidate the pathophysiology of the disease and its clinical implications to develop therapies and alternative treatments to improve the quality of life and increase longevity of DMD patients. This review presents an overview of relevant contributions of the DGR model for elucidating DMD in humans.
Relevant aspects of golden retriever muscular dystrophy for the study of duchenne muscular dystrophy in humans
Keywords: Animal model; Duchenne muscular dystrophy; Dystrophic golden retriever